Rectifier for Wireless Power Transfer (WPT) / Muhd Ikram Aziz and Muhammad Aliff Azmi - Aziz, Muhd Ikram; Azmi, Muhammad Aliff (2019)
A rectifier is an electrical device that converts alternating current (AC), which periodically reverses direction, to direct current (DC), which flows in only one direction. Rectifiers have many uses, but are often found serving as components of DC power supplies and high-voltage direct current power transmission systems. Rectification may serve in roles other than to generate direct current for use as a source of power. This project presents a full wave rectification. This project will use the full wave bridge rectifier. A full-wave rectifier converts the whole of the input waveform to one of constant polarity (positive or negative) at its output. Mathematically, this corresponds to the absolute value function. Two coil will be put parallel each other for wireless power transfer. One coil at the output supply circuit and the other at input load circuit. In order to verify the circuit, a simulation and system prototype of the wireless power transfer system has been built and implemented. The receiving power at different lateral offset between primary coil and secondary coil was also measured. The simulated and experimental results confirmed that the proposed system makes it possible to apply for the wireless connection activate the Bulb.